Geomorphological heritage inventory of Irazú Volcano, Costa Rica - Pérez Umaña, Dennis (2020)
Volcanoes are part of the natural environment, and the interactions with humans are inescapable. The geoheritage studies in tropical regions, specifically tropical volcanos, are scarce despite the uniqueness, scientific value, and beauty of these features. We performed an integrated approach for the inventory and management of the geomorphological heritage of the Irazú Volcano National Park, one of the most visited parks in Costa Rica. We identified eleven geomorphosites including volcanic craters, hills, domes, lagoons, and caves. The average in the assessment of scientific values of all the identified geomorphosites was 0.67. The site that rated the highest average between all the geomorphosites (0.94) was the Principal Crater. Other geomorphosites with high average and similar conditions were Diego de la Haya Crater, Playa Hermosa Crater and Sapper Hill, which show outstanding characteristics. Irazú volcano has an exuberant geodiversity and this assessment shows its geological and cultural richness. This demonstrates the importance and value that the volcano poses for the geoheritage of Costa Rica, Central America and tropical regions.